2016
DOI: 10.3762/bjnano.7.60
|View full text |Cite
|
Sign up to set email alerts
|

Tight junction between endothelial cells: the interaction between nanoparticles and blood vessels

Abstract: SummarySince nanoparticles are now widely applied as food additives, in cosmetics and other industries, especially in medical therapy and diagnosis, we ask here whether nanoparticles can cause several adverse effects to human health. In this review, based on research on nanotoxicity, we mainly discuss the negative influence of nanoparticles on blood vessels in several aspects and the potential mechanism for nanoparticles to penetrate endothelial layers of blood vessels, which are the sites of phosphorylation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 103 publications
0
14
0
Order By: Relevance
“…NPs may also transport across ECs to targets via exocytosis (Oh and Park, ; Frohlich, ) or paracellular pathways through the regulation of junction proteins (Fig. ) (Zhang and Yang, ). Exocytosis by HUVECs has been observed after exposure to mesoporous silica NPs (Slowing et al, ), peptide functionalized Au NPs (Bartczak et al, ) and silicon QD (Ohta et al, ).…”
Section: Interactions Between Nps and Huvecsmentioning
confidence: 99%
“…NPs may also transport across ECs to targets via exocytosis (Oh and Park, ; Frohlich, ) or paracellular pathways through the regulation of junction proteins (Fig. ) (Zhang and Yang, ). Exocytosis by HUVECs has been observed after exposure to mesoporous silica NPs (Slowing et al, ), peptide functionalized Au NPs (Bartczak et al, ) and silicon QD (Ohta et al, ).…”
Section: Interactions Between Nps and Huvecsmentioning
confidence: 99%
“…[21][22][23] Among these, endothelial cells constitute one of the very first barriers that nanomedicines need to overcome in order to reach the targeted organ following administration into the blood stream. 24,25 In order to control access to the underlying tissue and impair the passage of pathogens and undesired molecules, endothelial cells are typically organized in cellular barriers expressing tight junctions among cells, and with a clear spatial and functional separation between their apical and basolateral membranes. 26 As a result, endocytic pathways are differentially expressed between the two sides of the cell monolayer.…”
Section: Introductionmentioning
confidence: 99%
“…They can also induce inflammation and cytotoxicity in endothelial cells through the activation of potassium channels [103]. Moreover, it has been suggested that nanoparticles can regulate the barrier function of tight junction (occludins, claudins, and ZO proteins) because they interact with key kinases, altering not only the oxidative status around the junction between endothelial cells but also altering the blood flow into the vessel [110]. These data indicate that nanoparticle/endothelial cell interaction can modify the function of the blood vessel, whether in the site of injection at the moment of intravenous administration, during the distribution process, or when directed toward specific targets.…”
Section: Interaction Of Nanomaterials With the Vascular Endotheliummentioning
confidence: 99%